Corpus stylistic analysis of postmodern narrative features in Mario Vargas Llosa’s The Feast of the Goat - Dalfino, Divine; Allamneni, Sharada; Cupery, Maria Pritchett (Humanities, Arts and Social Sciences Studies, 2023)
By deploying a computational toolkit, this paper carries out a corpus stylistic analysis to understand the postmodern narrative features in Mario Vargas Llosa’s The Feast of the Goat. Since a novel’s style is mostly determined by the authors’ choice of literary techniques, a stylistic analysis would help to uncover the features of a text, particularly the language and literary techniques employed in it. It is evident Llosa employs postmodern narrative techniques to counter the prevailing narrative that Trujillo's regime was one of great economic prosperity and wellbeing for the Dominican Republic. The paper adopted a corpus methodology for uncovering, quantitatively as well as qualitatively, certain features of the postmodern narrative in The Feast of the Goat, features that normally get missed out in a manual analysis. AntConc corpus software was adopted for the study to explore how use of certain key words, as well as semantic domains could help to understand Llosa’s narrative techniques, particularly his use of flashbacks and fragmentariness, besides character-delineation in relation to the key themes of the novel like surveillance and dictatorship. While the quantitative data provided a helpful starting point, further analysis tied the findings to the central themes of the novel, as not all words in the text have straightforward interpretations. Thus, a corpus analysis of The Feast of the Goat deepens our understanding of how Llosa creatively incorporates postmodern techniques to reconstruct the inner working of the dictator's mind. His ruminations serve as the narrative framework for the novel. Through an analysis of linguistic data, we unveil the writer’s style in detail, to exemplify what type of reader response the authors hopes to elicit through the adoption of such stylistic devices.